Impact of urban and peri-urban landscape on local climate conditions – the case study of the city of Bragança (Portugal) - 2012-2016 - Gonçalves, Artur (2020)
In cities, buildings and paved surfaces change local climate conditions, generating the so called urban climate (Oke, 2004). Urban climate is also influenced by local orography and regional climate. One of the most important urban effects on climate is known as the urban heat island effect (UHI), measured as the difference in temperature between the urban context and the rural surroundings. Research on city/climate interactions can be an important contribution for urban planning, helping to address the negative effects of urbanization (Oke, 2004; Ren et al., 2010) Starting in 2011, as part of a transnational project BIOURB (INTERREG-POCTEP), a study is being carried out aiming at analysing the urban climate of Bragança (Portugal) (Gonçalves et al., 2014), a city located in a mountain area with a complex terrain. This presentation focuses on demonstrating the local influence of the urban and periurban landscape on local climate and evaluating possible planning options that can help improving urban climate. The research consists on a cross-evaluation between meteorological data, gathered from a local network of sensors (23 temperature andhumidity sensors, three wind speed and direction sensors and one automatic weather station) and a GIS analysis of the urban and topographical elements. This network covers seven local climate zones, including urban, peri-urban and rural sites. Results show that despite the small size of the city of Bragança (aprox. 25.000 hab. and 12 sq. km2) there is a mean UHI that reached 3 ºC in the summer with extremes of up to 6º C. Such results are related with the characteristics of the monitored sites and, as expected, UHI is more intense in densely urbanized areas. Other local effects include the presence of an altitude gradient (corrected for UHI analysis) and dynamical processes, such as the nocturnal drainage of cold air. Reduced UHI intensity was achieved in Urban Green Spaces, more effective during summer periods, mostly motivated by the presence of deciduous trees. Despite these positive effects, the studied green spaces are still under the influence of the UHI, being warmer than peri-urban locations. The complex mountain terrain was responsible for differences related to landscape attributes which should be taken into consideration in planning. Therefore recommendations are presented, including the role of the urban green infrastructure as a tool to improve the local climate conditions in the city (summer cooling and attenuated cold temperature effects). Gonçalves, A., Ribeiro, A. C., Maia, F., & Feliciano, M. (2014). Clima Urbano de Bragança. In A. Gonçalves (Ed.): Instituto Politécnico de Bragança. Oke, T. R. (2004). Initial guidance to obtain representative meteorological observations at urban sites: World Meteorological Organization Geneva. Ren, C., Ng, E. Y.-y., & Katzschner, L. (2010). Urban climatic map studies: a review. International Journal of Climatology, n/a-n/a. doi: 10.1002/joc.2237